2013
DOI: 10.1002/ange.201307665
|View full text |Cite
|
Sign up to set email alerts
|

A Reusable Unsupported Rhenium Nanocrystalline Catalyst for Acceptorless Dehydrogenation of Alcohols through γ‐C–H Activation

Abstract: Rhenium nanocrystalline particles (Re NPs), of 2 nm size, were prepared from NH 4 ReO 4 under mild conditions in neat alcohol. The unsupported Re NPs convert secondary and benzylic alcohols to ketones and aldehydes, respectively, through catalytic acceptorless dehydrogenation (AD). The oxidant-and acceptor-free neat dehydrogenation of alcohols to obtain dihydrogen gas is a green and atomeconomical process for making carbonyl compounds. Secondary aliphatic alcohols give quantitative conversion and yield. Transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…Primary alcohols and diols were not as effective. This is in agreement with ReO x NPs acting as a dehydrogenation catalyst for alcohols and having the highest activity with secondary alcohols as has been noted previously . The effect of 3-octanol versus glycerol concentrations on the DODH reaction was investigated in the range of [glycerol] = 0.6–4.2 M (Figure S2b).…”
Section: Results and Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Primary alcohols and diols were not as effective. This is in agreement with ReO x NPs acting as a dehydrogenation catalyst for alcohols and having the highest activity with secondary alcohols as has been noted previously . The effect of 3-octanol versus glycerol concentrations on the DODH reaction was investigated in the range of [glycerol] = 0.6–4.2 M (Figure S2b).…”
Section: Results and Discussionsupporting
confidence: 88%
“…For the homogeneous methyltrioxorhenium (MTO) DODH catalyst with glycerol as both substrate and reductant, the KIE of d 5 -glycerol–(OH) 3 was reported to be 2.4, indicating involvement of the C–H/D bond of glycerol in the rate-determining step . Reduction of Re species in DODH reaction in the presence of 3-octanol is associated with dehydrogenation of 3-octanol by ReO x NPs to give 3-octanone . In this study, glycerol–(OD) 3 in the presence of either 3-octanol or 3-(OD)-octanol showed no kinetic isotope effect (Figure S14).…”
Section: Results and Discussionmentioning
confidence: 65%
See 3 more Smart Citations